Evolution of the Chos Malal and Agrio fold and thrust belts, Andes of Neuquén: insights from structural analysis and apatite fission track dating - Rojas Vera, Emilio Agustin (2015)
The Chos Malal and Agrio fold and thrust belts are located in the western part of the Neuquén basin, an Andean retroarc basin of central-western Argentina. Both belts show evidence of tectonic inversion at the western part during Late Cretaceous times. The eastern part is dominated by late Miocene deformation which also partially reactivated the western structures. This work focuses on the study of the regional structure and the deformational event that shaped the relief of this part of the Andes. Based on new field work and structural data and previously published works a detailed map of the central part of the Neuquén basin is presented. Three regional structural cross sections were surveyed and balanced using the 2d Move™ software. In order to define a more accurate uplift history, new apatite fission track analyses were carried on selected structures. These data was used for new thermal history modeling of the inner part of the Agrio and Chos Malal fold and thrust belts. The results of the fission track analyses improve the knowledge of how these fold and thrust belts have grown trough time. Two main deformational events are defined in Late Cretaceous to Paleocene and Late Miocene times. Based on this regional structural analysis and the fission track data the precise location of the orogenic front for the Late Cretaceous-Paleocene times is reconstructed and it is proposed a structural evolution of this segment of the Andes. This new exhumation data show how the Late Cretaceous to Paleocene event was a continuous and uninterrupted deformational event.